A Comparison of Zoo Animal Behavior in the Presence of Familiar and Unfamiliar People. Issue 3 (2nd July 2016) - Martin, Rosemary Anne; Melfi, Vicky
Abstract : As recorded in domestic nonhuman animals, regular interactions between animals in zoos and keepers and the resulting relationship formed (human–animal relationship [HAR]) are likely to influence the animals' behaviors with associated welfare consequences. HAR formation requires that zoo animals distinguish between familiar and unfamiliar people. This ability was tested by comparing zoo animal behavioral responses to familiar (routine) keepers and unfamiliar keepers (participants in the "Keeper for the Day" program). Study subjects included 1 African elephant ( Loxodonta Africana ), 3 Rothschild's giraffes ( Giraffa camelopardalis rothschildi ), 2 Brazilian tapir ( Tapirus terrestris ), and 2 slender-tailed meerkats ( Suricata suricatta ). Different behavior was evident and observed as decreased avoidance behavior toward familiar keepers ( t 7  = 6.00, p <  .001). This finding suggests the zoo animals have a lower level of fear toward familiar keepers. Keeper familiarity did not significantly affect any other behavioral measure. This finding suggests that in the current study, unfamiliar keeper presence did not appear to have detrimental effects. Furthermore, unfamiliar keeper–animal interactions could provide an increased number of positive human–animal interactions and potentially enhance animal welfare.